Post‐engraftment blood transfusion and outcomes of bone marrow transplantation. (21st December 2015) - Mashimo, Y.; Ikeda, K.; Ohkawara, H.; Takahashi, H.; Shichishima‐Nakamura, A.; Furukawa, M.; Kimura, S.; Ueda, K.; Noji, H.; Ogawa, K.; Nollet, K. E.; Ohto, H.; et al.
Abstract : Background and Objectives: Red blood cell (RBC) transfusion prior to allogeneic hematopoietic stem cell transplantation (allo‐HSCT) is linked to poor outcomes, but outcomes related to post‐transplant, especially postengraftment transfusions, have not been fully investigated. We investigated allo‐HSCT outcome in association with early postengraftment transfusion. Materials and Methods: We reviewed RBC and platelet transfusions in 50 recipients of bone marrow transplantation, specifically analysing postengraftment transfusions from 31 to 60 days post‐transplant with no relapse in our institution. Results: Postengraftment RBC and/or platelet transfusions were needed in 22 (44·0%) patients. Pretransplant haemoglobin concentrations were negatively correlated with RBC transfusions performed from days 0 to 30, but not postengraftment. Regardless of product type, transfused patients were more anaemic and thrombocytopenic even at day 100, when most of them no longer required transfusion. Patients with postengraftment transfusions, especially those who were transfused both RBC and platelet, showed inferior overall survival ( P = 0·016) with increases of both chronic graft‐versus‐host disease and relapse ( P = 0·002 and 0·019, respectively). Postengraftment RBC and platelet transfusion were significant predictors for poor survival in multivariable analysis. Conclusions: Postengraftment transfusion may be associated with adverse outcomes of allo‐HSCT.